"I wonder what lies beyond that horizon?". Issue 3 (November 2018) - Fergie, Doseena
The horizon can mean many things to individuals. The author gives an account of those within her 'sphere of influence' who enabled her to stand on their broad shoulders to face the challenges and bask in the joys within the tertiary sector and, around the world. Having been raised in an atmosphere of colonisation where assimilation was the norm, the writer extrapolates her encounter with the education system to find her 'true' identity and place within the 'system'. How does one transfer the learnings of living in 'two worlds' to a largely non-Indigenous student cohort? How can one remain true to oneself when writing a PhD thesis within a Western system? Finally, as a Churchill Fellowship recipient, the writer travelled the world to seek out how other Indigenous nations around the world have found ways to heal the wounds of colonisation. This writer has experienced the horizon as both a challenger and a nurturer of knowledge.